DCC-GARCH Application in Formulating Dynamic Portfolio between Stocks in the Indonesia Stock Exchange with Gold - Robiyanto, Robiyanto (UI Scholars Hub, 2018)
This study tries to form a portfolio by using a method which may accommodate the dynamic of assets correlation and the abnormality of stock return distribution namely DCC-GARCH. The objective of this study is to combine individual stocks with gold, so retail investor can also apply this method. This study using data from January 2009 –December 2017 period. Samples in this study were nine stocks. The results of this study showed that there were two stocks with higher Sharpe Ratio if combined with gold through dynamic portfolio formation (hedged portfolio) namely BBCA-Gold and SMCB-Gold than unhedged portfolio. And there are three stocks with higher Treynor Ratio if combined with gold through dynamic portfolio formation (hedged portfolio) namely BBCA-Gold, SMCB-Gold and UNTR-Gold than unhedged portfolio. This finding proves that the DCC-GARCH application can improve the risk-adjusted return of these stocks when combined with gold